Optimizing nutrient utilization in beef cattle: the effects of narasin and rumen-protected methionine supplementation - Lelis, Ana Laura Januario [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This study addresses nutritional strategies aimed at intensifying beef cattle production through the use of feed additives to improve feed efficiency, ruminal health, and productive performance. Chapters 2 and 3 present two studies with this purpose. Chapter 2 aimed to evaluate the effects of different doses of narasin (13, 20, and 27 ppm) on ruminal fermentation, microbial composition, and nutrient digestibility in rumen-cannulated Angus steers fed a finishing diet containing 87% concentrate. The experiment followed a 3×3 duplicated Latin square design. Narasin supplementation enhanced ruminal pH stability, promoted beneficial changes in microbial diversity, and improved ruminal papillae morphology, especially at doses of 13 and 20 ppm. The intermediate dose (20 ppm) stood out by providing greater microbial diversity and ruminal stability. Conversely, the highest dose (27 ppm) reduced volatile fatty acid production and microbial diversity, suggesting an excessive antimicrobial effect. Acid detergent fiber digestibility improved with 27 ppm, although no significant impact on ruminal degradability was observed. Therefore, doses between 13 and 20 ppm are recommended, with 20 ppm being ideal under less controlled nutritional management. In Chapter 3, the impact of adding rumen-protected methionine (RPM) to supplementation protocols for crossbred heifers (½ Angus × ½ Nellore) finished on pasture was evaluated. The randomized block design included 48 animals distributed across 12 paddocks of Urochloa brizantha cv. Marandu and subjected to three supplementation protocols with different levels of energy supplementation, with or without rumen-protected methionine (RPM). Although no significant differences in productive performance were observed among treatments, heifers supplemented with methionine exhibited a larger rib eye area at the end of the study and lower fat deposition in the Biceps femoris muscle, highlighting improvements in carcass quality. RPM supplementation promoted histological changes in the cecum, indicating improvements in intestinal health and nutrient absorption potential. These findings suggest that RPM can optimize supplementation strategies in pasture-based systems, especially when combined with a gradual reduction in initial concentrate supply. Overall, the results demonstrate that the strategic use of additives such as narasin and rumen-protected methionine contributes to more efficient production systems capable of meeting the growing demand for high-quality beef.

O presente trabalho aborda estratégias nutricionais voltadas à intensificação da bovinocultura de corte, com ênfase no uso de aditivos alimentares para melhorar a eficiência alimentar, a saúde ruminal e o desempenho produtivo dos animais. Os capítulos 2 e 3 apresentam dois estudos com essa finalidade. No capítulo 2, o objetivo foi avaliar os efeitos de diferentes doses de narasina (13, 20 e 27 ppm) sobre a fermentação ruminal, composição da microbiota e digestibilidade de nutrientes em bovinos Angus canulados, confinados e alimentados com dieta contendo 87% de concentrado. O experimento foi conduzido em delineamento quadrado latino 3×3 duplicado. A suplementação com narasina aumentou a estabilidade do pH ruminal, promoveu alterações benéficas na diversidade microbiana e favoreceu o desenvolvimento morfológico das papilas ruminais, especialmente nas doses de 13 e 20 ppm. A dose intermediária (20 ppm) destacou-se por conferir maior diversidade bacteriana e estabilidade do ambiente ruminal. Em contrapartida, a dose mais elevada (27 ppm) resultou em menor produção de ácidos graxos voláteis e redução da diversidade microbiana, sugerindo efeito antimicrobiano excessivo. A digestibilidade da fibra em detergente ácido foi favorecida com 27 ppm, embora sem impacto significativo sobre a degradabilidade ruminal. Conclui-se que doses entre 13 e 20 ppm são mais recomendadas, com 20 ppm sendo ideal para situações de manejo nutricional menos rigoroso. No capítulo 3, investigou-se o impacto da inclusão de metionina protegida ao rúmen (RPM) em protocolos de suplementação para novilhas mestiças (½ Angus × ½ Nelore) terminadas a pasto em piquetes de Urochloa brizantha cv. Marandu. O delineamento foi em blocos casualizados com 48 animais distribuídos em 12 piquetes e submetidos a três níveis de suplementação com RPM. Embora não tenham sido observadas diferenças significativas no desempenho produtivo entre os tratamentos, as novilhas suplementadas com metionina apresentaram uma maior área do olho de lombo ao final do estudo e menor deposição de gordura no músculo Bíceps femoral, destacando melhorias na qualidade da carcaça. A suplementação com MPR promoveu alterações histológicas no ceco, indicando melhorias na saúde intestinal e no potencial de absorção de nutrientes. Esses achados sugerem que a MPR pode otimizar estratégias de suplementação em sistemas a pasto, especialmente quando combinada com uma redução gradual da oferta inicial de concentrado. De modo geral, os resultados demonstram que o uso estratégico de aditivos como a narasina e a metionina protegida no rúmen contribui para sistemas de produção mais eficientes capazes de atender à crescente demanda por carne bovina de alta qualidade.
Otimizando a utilização de nutrientes em bovinos de corte: os efeitos da suplementação com narasina e metionina protegida do rúmen
Keywords: Aditivo; Metionina; Narasina; Rumen